Sincerity as an Islamic Spiritual Competence: A Critical Analytical Study of the Dimensions of Sincerity - Jamaluddin, Mustafa Mohamed Abdelmohiman; Al Saied, Osama Abdullah; Salem, Abdullah Hussein; Sabra, Wael Ahmed Abdalla (Journal of Educational and Psychological Sciences, 2025)
The research aims to explore the fundamentals of sincerity in the Muslim’s heart, both in belief and thought, and in their actions and practices by studying the concept of sincerity in Islam, clarifying its effects on society, clarifying its foundations and domains, and identifying the cognitive and behavioral indicators resulting from the presence of sincerity in a Muslim's heart. It also identifies the patterns of thought, behavior, and learning outcomes associated with the presence of sincerity. The research then attempts to answer the main question: How can sincerity be instilled in Muslim’s heart, both in belief and thought, and in their actions and practices? The research utilizes the analytical inductive method to extrapolate and trace the legal evidence on sincerity from the Book of God Almighty and the Sunnah of His Messenger (peace and blessings be upon him), as well as what scholars have stated in this regard. The legal texts from the Holy Qur'an and the Prophetic Sunnah related to the competency of sincerity are extrapolated and analyzed through a framework of perception, feeling, and behavior. The research also utilizes the analytical scientific method, employing an organized plan to reach a conclusion, starting with the details and ending with the generalities, results, and implications. Therefore, the primary tool in this research is a content analysis of verses, hadiths, and contemporary studies that address the competency of sincerity.The study concluded, among its most important findings, that sincerity is derived from the verb (akhlaṣa), the present tense of which is (yukhlis), and its root (ikhlās), meaning to purify something, to make it pure and not mix anything else with it. A man purified his religion for God, meaning he made it purely for God. The study also concluded that building the habit of sincerity is linked to training, through choosing a simple act of worship to be performed individually, away from public view, and then continuing to perform it until it becomes a habit. The competency of sincerity also interacts within the young person, producing patterns of thinking and behavior characterized by positivity and sociability, without excess, isolation, or individualism.The study recommended the necessity of complementing the theoretical study of sincerity with applied programs through which sincerity can be instilled and applied through workshops and cognitive-behavioral programs for students in universities and schools, and courses for children and youth in clubs and mosques.
Keywords: Sincerity; the faithful; Islamic Competence; Spiritual Competence